To the question of scientific justification of the interests on deposits and credit - Pshinko, O. M.; Myamlin, V. V.; Myamlin, S. V. (Science and Transport Progress, 2013)
Purpose. To analyze the need of loans in the form they are presented today at the present stage of economic functioning. To develop a systematic group of actions in order to allow the “economic and financial” system of the country to work efficiently, irrespective of economic and financial world cataclysms. Methodology. Computer simulation model of monetary movement in the state is developed and tested. Conclusions. A retrospective analysis of the essence of theories of credit and lending rate has been made. Some aspects of interest receiving on deposits and loans from the point of view of a radically new economic model of management, which based on the "National economy high-performance theory», are considered. Using the simulation modeling the negative influence of bank interest on the national economy general development is indicated. It is proved that the main reason of the “financial and economic crisis” is the economic category of “profit”. Originality. A radically new model of banking system functioning in the country is proposed. This system allows one to create synergistic economic effect. Practical value. Implementation of the given model will provide the GDP growth for the 2–2.5 times as early as the first years. The economic effect of the introduction can bring about 1 trillion UAH.